Super-Resolution Molecular and Functional Imaging of Nanoscale Architectures in Life and Materials Science - Habuchi, Satoshi (Frontiers in Bioengineering and Biotechnology, 2014)
Super-resolution fluorescence microscopy has been revolutionizing the way in which we investigate the structures, dynamics, and functions of a wide range of nanoscale systems. In this review, I describe the current state of various super-resolution fluorescence microscopy techniques along with the latest developments of fluorophores and labeling for the super-resolution microscopy. I discuss the applications of super-resolution microscopy in the fields of life science and materials science with a special emphasis on quantitative molecular imaging and nanoscale functional imaging. These studies open new opportunities for unraveling the physical, chemical, and optical properties of a wide range of nanoscale architectures together with their nanostructures and will enable the development of new (bio-)nanotechnology.